Impact of ownerships and control on internet financial reporting - Gunawan, Gregorius; Sanjaya, I Putu Sugiartha (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2021)
The objective of this study is to empirically investigate the impacts of ownerships (managerial ownership and institutional ownership) and control (number of independent commissioners, frequency of audit committee meeting, and audit committee competence) on Internet Financial Reporting (IFR). This study was conducted on manufacturing companies listed at the Indonesian Stock Exchange (BEI) in 2015-2019. This study used secondary data, namely annual financial statements which were accessed through the companies’ websites. The firm years counted 200 with 40 companies and 5 years of research duration. The dependent variable is IFR which analyzed the contents of the websites with the maximum score of 54. The independent variables are managerial ownership, institutional ownership, number of independent commissioners, frequency of audit committee meeting, and competence of audit committee. The results show that institutional ownership, frequency of audit committee meeting, and audit committee competence have significantly and positively influences on IFR. However, institutional ownership negatively affects IFR. Meanwhile, number of independent commissioners does not influence internet financial reporting.